INFECTIOUS COMPLICATIONS AFTER UMBILICAL CORD-BLOOD TRANSPLANTATION FROM UNRELATED DONORS - Juan Montoro; Jaime Sanz (Mediterranean Journal of Hematology and Infectious Diseases)
Umbilical cord-blood (UCB) is a well-recognized alternative source of stem cells for unrelated donor hematopoietic stem cell transplantation (HSCT). As compared with other stem cell sources from adult donors, it has the advantages of immediate availability of cells, absence of risk to the donor and reduced risk of graft-versus-host disease despite donor-recipient HLA disparity. However, the use of UCB is limited by the delayed post-transplant hematologic recovery due, at least in part, to the reduced number of hematopoietic cells in the graft and the delayed or incomplete immune reconstitution. As a result, severe infectious complications continue to be a leading cause of morbidity and mortality following UCB transplantation (UCBT). We will address the complex differences in the immune properties of UCB and review the incidence, characteristics, risk factors, and severity of bacterial, fungal and viral infectious complications in patients undergoing UCBT.